Dimensi Kepercayaan dalam Usaha Pelepas Uang (Studi Kasus di Kabupaten Semarang) - Yustinus Wahyudi; Gatot Sasongko (Jurnal Sosial Humaniora, 2019)
The informality of the money lender business is closely related to transactioncosts and risks in carrying out its business. Trust is vital and plays animportant role in the sustainability of money lender businesses. Trust serves toreduce transaction costs, mortgage loan risks and the determination ofcollateral. This study will look at the role of trust dimensions, namely ability,benevolence, and integrity in money lender loan transactions in SemarangRegency. To achieve this goal, the research uses a qualitative approach withcase studies, which aims to comprehensively understand the role of thedimensions of trust in lending transactions in money lender businesses.Without business chains such as farmers and middlemen, fishermen andbosses as well as traders and moneylenders, the money-releasing business inSemarang Regency is able to develop trust with their customers. In addition,moneylenders provide loans for consumptive purposes.